Environmental hazards and waste management in Nsukka urban metropolis in Enugu State of Nigeria: how much are people willing to pay?. (1st January 2018) - Nwosu, Emmanuel O.; Orji, Anthony; Yuni, Denis
ABSTRACT: Solid waste management in Nsukka town in Enugu state of Nigeria has remained a major challenge despite the efforts of the state government through the Enugu State Waste Management Agency (ESWAMA). The current method whereby households dump refuse at designated locations by the road side to be cleared later has not yielded much improved sanitation of the town. In this study we propose an alternative waste management method that is believed to be superior to the status quo if properly managed. This study applies Contingent Valuation Method (CVM) to estimate the households' willingness to pay (WTP) for this new method in order to ascertain its applicability in Nsukka urban. Data were collected from a sample of 500 households stratified according to major streets in the town. The results show that the mean WTP using different specifications of the model varies from N527.50 (about 2.68) to N530.90 (about 2.68) per month. The policy implication is that if the waste management agency adopts the proposed scenario and manages it well the average revenue realizable per month would be about N13, 750, 516 (about $69, 800). The authorities can compare this with the cost of providing the service and see if it is worth the effort.